การตรวจหาสารพฤกษเคมีและฤทธิ์ต้านจุลินทรีย์ของสารสกัดเท้ายายม่อม (Tacca leontopetaloides (L.) Kuntze.) PHYSICOCHEMICAL AND ANTIMICROBIAL ACTIVITY OF THAO YAI MOM (TACCA LEONTOPETALOIDES (L.) KUNTZE.) EXTRACTS - วัชรเทวินทร์กุล ญาณิกา; เรียงหมู่ อานนท์ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Phytochemical screening of Thao Yai Mom (Tacca leontopetaloides (L.) Kuntze) indicated that its flour extracts contained alkaloids, saponins, flavonoids and tannins. These compounds except alkaloids were also found in the peel extracts. The ferric chloride test could not detect phenolic in both extracts. Total phenolic contents of the flour and peel extracts determined by Folin-Ciocalteu colorimetric method were 2.70 and 8.11 mg GAE/g dry sample, respectively. Tannins were evaluated at 2.62 and 8.68 mg TAE/g dry sample of flour and peel, respectively. Whereas total flavonoid content of the peel extracts was 20.79 mg QE/g dry sample, which was about 26 times higher than that of the flour extracts (0.79 mg QE/g dry sample). The significant microbial growth inhibition, tested with broth dilution method, by the peel extracts were observed for Candida lipolytica at 99.70%, Bacillus subtilis at 76.58%, Enterococcus faecalis TISTR 379 at 72.79%, Staphylococcus aureus at 69.23% and Salmonella sp. at 56.92%. Other gram-negative bacteria, Pseudomonas fluorescens TISTR 904 and Escherichia coli showed much more resistant to the peel extracts than Salmonella sp. The flour extracts possessed less potential antimicrobial activity than the peel extracts and gave significant inhibition only on C. lipolytica at 45.86% and E. faecalis TISTR 379 at 13.55%. The MIC test of peel extracts indicated that S. aureus was the most sensitive microorganism giving the lowest MIC value (12.5 mg/ml) followed by E. faecalis TISTR 379 and C. lipolytica (25 mg/ml) and B. subtilis (50 mg/ml), respectively. Gram-negative Salmonella sp. was observed less sensitive to the extracts with the highest MIC value (100 mg/ml). This study gave evidence that Thao Yai Mom might be applicable as natural source of antimicrobial agent.